Partisipasi Politik Kelompok Penyandang Disabilitas pada Pemilu Tahun 2024 Kota Payakumbuh Ditinjau dari Fiqh Siyasah - Oktarina, Soraya; Harahap, Mona Syariah (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2024)
Participation in elections is the right of all people, without exception. Disability groups are a vulnerable group that must be considered every time an election is held. In the 2024 elections, participation by disability groups in the city of Payakumbuh is experiencing an upward trend. This research aims to identify factors that can increase the participation of people with disabilities in the 2024 General Election (Pemilu) in Payakumbuh City, viewed from the perspective of siyasah fiqh. In the context of fiqh siyasah provides a basis for understanding political participation as part of social responsibility and religious obligation. This research uses a qualitative approach with a descriptive approach to analyze data collected through in-depth interviews, observations and relevant literature reviews. Based on the research results, it shows that the participation of people with disabilities in elections has been carried out from the initial stages until post-election, starting from actively participating in socialization, discussing the needs of disabled groups in elections, being open and collaborating with the organizers in the data collection stage, voting, to participating in monitoring the results. voting. From the perspective of fiqh sÄ±yasah, participation of persons with disabilities in elections is part of the rights and obligations of citizens to be involved in the political process, as well as efforts to realize justice and equality in state life.